Integrative analysis of circRNAs from Yangtze River Delta white goat neck skin tissue by high‐throughput sequencing (circRNA‐seq). (5th April 2022) - Wang, Jian; Wu, Xi; Kang, Yan; Zhang, Liuming; Niu, Haoyuan; Qu, Jingwen; Wang, Yanhu; Ji, Dejun; Li, Yongjun
Abstract: The Yangtze River Delta white goat is a unique goat species that can produce superior‐quality brush hair. The formation of this brush hair is controlled by a series of critical genes and related signaling pathways. Circular RNAs (circRNAs), are ubiquitous endogenous non‐coding RNAs that regulate many biological and physiological processes in mammals. However, little is known about the potential regulatory role of circRNAs on superior‐quality brush hair formation in Yangtze River Delta white goat. In this study, high‐throughput sequencing technology was used to only detect circRNAs in the neck skin tissue of normal‐quality goats (NHQs) and superior‐quality goats (HQs). A total of 61 803 circRNAs were identified and 32 of them were differentially expressed in the NHQ group vs. the HQ group. Functional enrichment analysis showed that the source gene of differentially expressed circRNAs (DE‐circRNAs) was enriched mostly in platelet activation and the focal adhesion signal pathway. Action mechanism analysis revealed that DE‐circRNAs could sponge to many identified miRNAs, including miR‐31, miR‐125b, miR‐let‐7a and miR‐149‐5p, which have important roles in goat hair follicle stem cell growth, hair follicle development and morphogenesis. Altogether, our findings provide a valuable basis for studying circRNAs involved in superior‐quality brush hair traits and meanwhile advance our understanding of circRNA complex regulation mechanisms in Yangtze River Delta white goat skin hair follicle development.